Synbiotic effect of L. fermentum PC1 and Spirulina on gut health and immunity - Sim, Edric Shao Zhe (Nanyang Technological University, 2021)
The modulation of the gut microbiome has been of great interest as the gut microbiome affects the host metabolism, and even establishing cross-talk with the immune system. Dietary interventions using probiotics, prebiotics and their combinations (synbiotics) have proven to be beneficial for human health. However, the mechanisms of synbiotics on the gut microbiome and immunity remains poorly characterized. Using an ex-vivo gut model supplemented with fecal samples, we hereby report that the combination of Lactobacillus fermentum PC1 and Spirulina as a synbiotic modulates the gut microbiome by promoting lactobacilli growth, exhibiting anti-microbial activity on enteric bacteria and enhancing acetic acid production. Using an in-vitro FMS-like tyrosine kinase 3 ligand (FLT3L)-stimulated bone-marrow dendritic cells (BMDCs), we also report that synbiotic differently upregulates dendritic cells (DCs) maturation and induce pro-inflammatory TNF-α, IL-6, IL-1β cytokines. Interestingly, synergism was only observed in the production of IL-1β cytokine. This might represent an alternative mechanism for synbiotic effects, other than the microbiota-driven modulation of immunity. Together, these findings successfully characterize synbiotic effects on gut health and immunity. However, the functionality of this synbiotic should be studied further in various in-vitro and in-vivo models, potentially paving way for precision application to individuals in clinical settings.